Electromagnetic Metamaterials Modern Insights into Macroscopic Electromagnetic Fields - Sakoda, Kazuaki (Springer Series in Materials Science, 2019)
This book presents novel and fundamental aspects of metamaterials, which have been overlooked in most previous publications, including chirality, non-reciprocity, and the Dirac-cone formation. It also describes the cutting-edge achievements of experimental studies in the last several years: the development of high-regularity metasurfaces in optical frequencies, high-performance components in the terahertz range, and active, chiral, nonlinear and non-reciprocal metamaterials in the microwave range. Presented here are unique features such as tunable metamaterials based on the discharge plasma, selective thermal emission from plasmonic metasurfaces, and the classical analogue of the electromagnetically induced transparency. These most advanced research achievements are explained in understandable terms by experts in each topic. The descriptions with many practical examples facilitate learning, and not only researchers and experts in this field but also graduate students can read the book without difficulty. The reader finds how these new concepts and new developments are being utilized for practical applications.